Progress in reducing road-related deaths and injuries in irish children. (4th April 2011) - Donnelly, J; Bimpeh, Y; Trace, F; Waters, A; Nicholson, A J
Abstract : Aims: Study road-related injuries and fatalities in under 15 year olds in two periods (1996–2000 and 2004–2008) to assess whether progress has been made via campaigns to reduce these numbers in Ireland. Methods: For road related accidents requiring police assistance a CT 68 form is completed by the officer and sent to the National Roads Authority. Details about injury severity, road conditions and safety measures, for example, seat belt use were recorded. Injuries were sub-classified as fatalities, serious or minor. All data for the two periods was entered into an SPSS database. A national road safety campaign involving random breath testing, penalty points, immediate fines and increased police enforcement took place between the two time frames and continues currently. Results: From 1996 to 2000, of 5928 road-related injuries, 153 were fatal, 712 serious and 5063 minor. From 2004–2008 of 3659, 82 were fatal, 347 serious and 3230 minor. In this second cohort, 59% were vehicle occupants, 33.8% pedestrians, 6% pedal cyclists and 0.6% used a moped or motorcycle, mirroring proportions in the first cohort. Car occupant fatalities dropped from 69 to 44. From 1996 to 2000 there were 69 car fatalities, 5 were drivers, 22 front seat passengers and 42 rear seat passengers. From 2004 to 2008, of 44 car fatalities, 2 were drivers, 12 front passengers and 30 rear passengers. The 13–15 age group had the highest mortality and morbidity in both cohorts. Documented restraint use was 23% in the first cohort and 34% in the second cohort. Pearson χ 2 tests confirmed a significant relationship between the use of an appropriate child restraint and the severity of injury (p<0.001). Pedestrian injuries dropped from 1719 to 1232, pedestrian fatalities halved as did serious pedestrian injuries (261 down to 129). Cyclist injuries also decreased with a dramatic reduction in cyclist fatalities from 25 down to 6. Conclusions: A national road safety campaign, greater police enforcement and a cultural change has seen road-related injuries in children drop very significantly (by over 60%) over the two time periods and this campaign should continue.